Measuring the association between hippocampal volume and memory abilities vulnerable to Alzheimer's disease in typically developing periadolescent children: Preliminary findings from the PRANK Study. (31st December 2021) - Sexton, Jennifer N; Phipps, Connor J; Behm, Lillian; DeCesare, Thomas A; Heller, Abi M; Maerlender, Arthur C.; Phatak, Vaishali S; Cramer, Justin A.; Blair, James; Murman, Daniel L; Warren, David E
Abstract: Background: Childhood development, including the periadolescent period, is associated with significant changes in brain function, brain structure, and cognition. Memory ability, including memory for arbitrary relations, exemplifies cognitive changes that occur during the periadolescent epoch. In adults, declarative/relational memory requires the hippocampus, as demonstrated by the profound memory impairments accompanying hippocampal pathology frequently caused by Alzheimer's disease (AD). Vulnerability to AD and related memory impairments in late life could be a function of early‐life brain development. Understanding the developmental relationship between hippocampal volume and declarative/relational memory performance would provide any important baseline for comparison of different trajectories. Our ongoing NIA‐funded research project, the Polygenic Risk of Alzheimer's Disease in Nebraska Kids (PRANK) study, measures brain structure, brain function, cognitive abilities, and Alzheimer's polygenic risk score in periadolescent children (age 8‐13). Here, we report preliminary data measuring the association between hippocampal volume and memory abilities in the study's periadolescent sample. Method: A sample of periadolescent children from the PRANK study provided data for the current project (N=40). Structural MRI data were collected using protocols adapted from the Human Connectome Project, and hippocampal volume was measured through manual tracing. Cognitive variables included relational memory operationalized as performance on the Picture Sequence Memory Task (PSMT) from the NIH Toolbox (a standard neuropsychological battery). We then tested the correlation between hippocampal volume and performance on the relational memory task in periadolescent children. Result: We found preliminary evidence consistent with differences in the neuropsychological profile and brain structure, specifically in hippocampal volume and declarative/relational memory performance. Our preliminary observations were consistent with significant correlations between regional hippocampal volume and memory performance on the PSMT. Conclusion: Findings from this preliminary analysis illustrate differences in cognitive abilities in the periadolescent period, in particular, the association between declarative/relational memory and hippocampal volume. Our ongoing PRANK study measures cognitive abilities, brain structure and function, and Alzheimer's polygenic risk score in periadolescent children. Future work from this study will investigate whether genetic risk for AD is associated with individual differences in brain structure and outcomes on neuropsychological measures in early life.